2020
DOI: 10.3390/s20113234
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of the (S)-BINAM Derivatives as Fluorescent Enantioselective Detectors

Abstract: Pd(0)-catalyzed amination was employed for the synthesis of a new family of (S)-1,1′-bianaphthalene-2,2′-diamine derivatives possessing additional chiral and fluorophore substituents. The Compounds thus obtained were tested as potential detectors of seven amino alcohols, and some of them were found to be able to recognize individual enantiomers of certain amino alcohols by specific changes of their emission spectra in the presence of these analytes. A pronounced dependence of the detecting abilities on the nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Earlier, we demonstrated that Pd-catalyzed amination of halogenoarenes could be used for one-step synthesis of various macrocycles in good yields [ 48 , 49 , 50 , 51 ]. Such macrocycles can be further developed into colorimetric [ 52 , 53 ] and fluorescent [ 54 , 55 , 56 ] chemosensors for metal cations detection, as well as for enantioselective recognition of chiral organic molecules [ 57 , 58 ]. In this work, we propose an approach to macrocyclic ligands on the basis of 6,7-annelated 2,3-diphenylquinoxaline and diazacrown ethers ( Figure 1 ) and show the results of the preliminary studies of their optical and sensing properties.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier, we demonstrated that Pd-catalyzed amination of halogenoarenes could be used for one-step synthesis of various macrocycles in good yields [ 48 , 49 , 50 , 51 ]. Such macrocycles can be further developed into colorimetric [ 52 , 53 ] and fluorescent [ 54 , 55 , 56 ] chemosensors for metal cations detection, as well as for enantioselective recognition of chiral organic molecules [ 57 , 58 ]. In this work, we propose an approach to macrocyclic ligands on the basis of 6,7-annelated 2,3-diphenylquinoxaline and diazacrown ethers ( Figure 1 ) and show the results of the preliminary studies of their optical and sensing properties.…”
Section: Introductionmentioning
confidence: 99%